2002
DOI: 10.1152/ajpheart.00291.2002
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of vagal efferent axon and nerve terminal function in the postischemic myocardium

Abstract: Despite the importance of vagal control over the ventricle, little is known regarding vagal efferent conduction and nerve terminal function in the postischemic myocardium. To elucidate postischemic changes in the cardiac vagal efferent neuronal function, we measured myocardial interstitial acetylcholine (ACh) levels by using in vivo cardiac microdialysis and examined the ACh responses to electrical stimulation of the vagi or local administration of ouabain in anesthetized cats. Sixty-minute occlusions of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Autonomic derangement occurs in the ischaemic myocardium. Disruption of vagal function also causes a deterioration of cardiac function 4,5 . Moreover, the reduction of vagal activity associated with ischaemic heart disease is independent of impaired coronary flow, immune system effects and hormonal effects.…”
Section: Alteration Of Vagal Tone In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic derangement occurs in the ischaemic myocardium. Disruption of vagal function also causes a deterioration of cardiac function 4,5 . Moreover, the reduction of vagal activity associated with ischaemic heart disease is independent of impaired coronary flow, immune system effects and hormonal effects.…”
Section: Alteration Of Vagal Tone In Cardiovascular Diseasesmentioning
confidence: 99%
“…Disruption of vagal function also causes a deterioration of cardiac function. 4,5 Moreover, the reduction of vagal activity associated with ischaemic heart disease is independent of impaired coronary flow, immune system effects and hormonal effects. A study in 68 patients has shown a sustained decrease in HRV 1 h ischaemic events, with HRV reaching a minimum at the onset of ischaemia, showing the extent of reduced vagal activity.…”
Section: Defective Cardiac Parasympathetic Control In Ischaemic Heartmentioning
confidence: 99%
“…While the effects of ischaemia and reperfusion on cardiac cell function have been the subject of many studies (Toda, 1969; Kourie, 1998; Carmeliet, 1999; Rodriguez et al 2006), there are few reports of their action on the intrinsic cardiac nervous system. The negative chronotropic action of vagal activation was blunted in a rat model of myocardial infarction (Du et al 1998), and the release of acetylcholine during vagal stimulation was abrogated by ischaemia in the anaesthetized dog (Kawada et al 2002). Accordingly, conditions simulating ischaemia, for example high K + , also attenuated the negative chronotropic action of vagal activation in the rat (Sears et al 1999).…”
mentioning
confidence: 99%
“…A disruption of vagal efferent neuronal function itself has also been shown in postischemic myocardium. 15 Recent experimental data suggest that baroreceptor depression is also mediated by a change in cardiac volume and/or compliance rather than simply by infarct size. 16 Consistent with that report, we observed a trend toward higher values for left ventricular end-diastolic filling pressure and lower values for left ventricular ejection fraction in TIMI 2 patients and moderate correlations of these hemodynamic parameters with HRT.…”
Section: Mi-associated Baroreceptor Depressionmentioning
confidence: 99%